PENGARUH MODEL PEMBELAJARAN SYNECTIC TERHADAP KREATIVITAS SENI DAN KEMAMPUAN MEMBUAT GAMBAR DEKORATIF SISWA KELAS X SMAN 1 KAMAL - Rediansyah, Andharta Yayang; Silver, Soesiana Tri Eka; Huda, Nuril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to analyze the influence of the synectic learning model on students' artistic creativity and ability to make decorative artworks. This research was conducted at SMA Negeri 1 Kamal in the 2024/2025 school year. The research method used is a quasi-experimental method with a randomize posttest only group control design. The research sample of 50 students consisted of 25 students in the experimental group and 25 students in the control group obtained by analysis independent sampel t test. The results of the study revealed that the artistic creativity and ability to make decorative artworks of students taught with a synectic learning model were higher than students taught with conventional learning. The conclusion of this study is that the use of synectic learning models affects students' artistic creativity and ability to make decorative artworks.